استثمار البيانات الضخمة وانعكاسها على مصادر وخدمات مركز الأزهر العالمي للفتوى الإلكترونية - بغدادي، أحمد إسماعيل (المؤسسة العربية لإدارة المعرفة, 2023)
تستهدف الدراسة استكشاف مجالات استثمار البيانات الضخمة وانعكاسها على مصادر وخدمات مركز الأزهر العالمي للفتوى الإلكترونية، وذلك في ضوء بيان مدى التأثير والانعكاس المرتبط بمصادر المعلومات وقنواتها المختلفة، وعائد الاستثمار في البيانات الضخمة وارتباطه بتطوير الخدمات المعلوماتية، وبيان معالم البنية التنظيمية والإدارية والتأثيرات المهنية والمعلوماتية المتعلقة بمجالات استثمار البيانات الضخمة، بينما توصلت الدراسة إلى عدة نتائج كان من أبرزها: إثبات فاعلية وتأثير الانعكاس المحدث من مجالات استثمار البيانات الضخمة في مصادر مركز الأزهر العالمي للفتوى الإلكترونية، بمعدلات متعددة فرضتها طبيعة البيانات الصادرة عن المركز، حيث جاءت بمؤشرات متباينة ما بين (20%- إلى- 52%) وهذا يبين مدى القابلية والتأثير المحدث في بيئة مصادر المعلومات الصادرة عن المركز في ضوء استثمار هذه البيانات كقيمة مضافة، كما بينت الدراسة قوة الانعكاس المتعلق بالخدمات وتطورها بمؤشرات ما بين (22%- إلى- 58%) وما بين (26%- إلى- 46%) وهذه المعطيات الإحصائية تبين مدى الفائدة المترتبة تجاه تنمية خدمات المعلومات بصورة مستدامة. بينما أظهرت الدراسة مدى الحاجة إلى أحداث تغيرات حتمية تتعلق بالبيئة التنظيمية والإدارية المتعلقة بعمليات إدارة واستثمار البيانات، ومن أبرز التوصيات التي قدمتها الدراسة: ضرورة العمل على سن تشريعات قانونية تختص بحقوق الملكية الفكرية وخصوصية البيانات المتعلقة بالأفراد في ضوء الاستخدام العادل للمعلومات، والإفادة منها في عدة اتجاهات معلوماتية ومعرفية، والقيام بتنمية الجوانب المهنية والتدريبية المتصلة بمجالات إدارة واستثمار البيانات من خلال برامج متخصصة لتأهيل الكوادر الحالية المتواجدة في المركز والاستعانة بالمتخصصين في مجال علوم البيانات وتقنيات المعلومات. كما اعتمدت المنهجية الدراسية على منهج دراسة الحالة باعتباره أفضل المناهج وأنسبها لهذه النوعية من الدراسات. The study aims to explore areas of investment in big data and its reflection on the sources and services of the Al-Azhar International Center for Electronic Fatwa, in light of the statement of the extent of influence and reflection related to information sources and its various channels, and to measure the return on investment in big data and its connection to the development of information services, and to indicate the features of the organizational and administrative structure, and the professional and informatics influences related to the areas of big data investment, while the study reached several results, the most prominent of which were: Evidence of the effectiveness and effect of the updated reflection from the areas of big data investment in the sources of the Al Azhar International Center for Electronic Fatwa, at multiple rates imposed by the nature of the data issued by the center, as it came with average indicators between ( 20% - to - 52%, and this indicates the extent of the ability and influence created in the environment of information sources issued by the center in light of the investment of this data as an added value to its informational sources, The study also showed the strength of reflection on services and their development, with indicators ranging from (-22% to -58%) and between (-26% to -46%). These statistical data show the extent of the benefit resulting from the development of information services in a sustainable manner. While the study showed the need for inevitable changes related to the regulatory and administrative environment related to data management and investment operations, and among the most prominent recommendations presented by the study: the need to work on enacting legal legislation related to intellectual property rights and the privacy of data related to individuals in light of the fair use of information, and to benefit from it in several ways Informatics and knowledge trends, and the development of professional and training aspects related to the fields of data management and investment through specialized programs to qualify the current cadres present in the center and the use of specialists in the field of data science and information technologies. The study methodology was also based on the case study approach as it is the best and most appropriate approach for this type of studies.
Keywords: الفتوى الإلكترونية -- استثمار البيانات -- البيانات الضخمة -- مركز الأزهر العالمي